(untitled) (Global Journal of Management and Business Research, 2023)
The notion of organizational citizenship behavior as an important variable has been recognized either by academicians or practitioners. However, the determinants of organizational citizenship behavior were still debatable. The purpose of this study was to investigate the role of affective commitment and psychological empowerment as mediating and moderating variables respectively. The numbers of usable respondents in this study were 64 employees at Staffing & Human Resources Development AgencyWest Sumatera, Indonesia. The results of the study revealed that transformational leadership had a positive and significant effect on affective commitment and organizational citizenship behavior. The variables of affective commitment and psychological empowerment were found to have a positive and significant effect on organizational citizenship behavior.